(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research tackled the attitude of interpretation towards the issue of metaphor, especially the French philosopher’s view Paul Ricuor. It also dealt with the nature of metaphor as suggested by him via critiquing the attitude in which he finds a mere aesthetic and substitutive ornament from the one hand, while taking it as innovative means to touch reality on the other hand. Consequently, it is a cognitive value with the aim of contacting the outside world and getting to know it then the research proceeded to discuss the intellectual basics of metaphor according to Ricuor. He noticed that there is no way to understand the nature of metaphor without understanding its basics. This has made it possible to handle the knowledgeable and innovative function of metaphor be it the present side always in language; that which never fades. So, it was not possible to handle metaphor inside language without wondering how thinking works. Here Ricuor differentiates between living and consumed metaphor on the basis of the ability of innovation and knowledge provided by each one of them. Additionally, he has stated that metaphor is there inside interpretation as it is through it. Such a presence of metaphor inside the field of interpretation is the reason why one can tackle this polysemy. This polysemy results in this on the one hand and in its openness on the world of human act; work and practice on the other hand. This way, metaphor in interpretation is presented as a future language. The research has ended up with a bunch of results through questioning the concept of metaphor in a philosophic interpretative way.